Communication in our lives - Wood, Julia T. (Cengage Learning, Inc., 2024)
"We use a conversational style of writing, and all chapters include examples, reflections from students, and applications that invite students to engage material personally. To help students develop their practical competence as communcators, we emphasize concrete skills and hands-on exercises."--Preface.